CD39 and CD326 Are Bona Fide Markers of Murine and Human Plasma Cells and Identify a Bone Marrow Specific Plasma Cell Subpopulation in Lupus - Dang, Van Duc; Mohr, Elodie; Szelinski, Franziska; Le, Tuan Anh; Ritter, Jacob; Hinnenthal, Timo; Stefanski, Ana-Luisa; Schrezenmeier, Eva; Ocvirk, Soeren; Hipfl, Christian; Hardt, Sebastian; Cheng, Qingyu; et al. (Frontiers in Immunology, 2022)
Antibody-secreting cells (ASCs) contribute to immunity through production of antibodies and cytokines. Identification of specific markers of ASC would allow selective targeting of these cells in several disease contexts. Here, we performed an unbiased, large-scale protein screening, and identified twelve new molecules that are specifically expressed by murine ASCs. Expression of these markers, particularly CD39, CD81, CD130, and CD326, is stable and offers an improved resolution for ASC identification. We accessed their expression in germ-free conditions and in T cell deficient mice, showing that at least in part their expression is controlled by microbial- and T cell-derived signals. Further analysis of lupus mice revealed the presence of a subpopulation of LAG-3– plasma cells, co-expressing high amounts of CD39 and CD326 in the bone marrow. This population was IgM+ and correlated with IgM anti-dsDNA autoantibodies in sera. Importantly, we found that CD39, CD81, CD130, and CD326 are also expressed by human peripheral blood and bone marrow ASCs. Our data provide innovative insights into ASC biology and function in mice and human, and identify an intriguing BM specific CD39++CD326++ ASC subpopulation in autoimmunity.